Quasi-experimental evidenceon the relationbetween child care subsidiesand child care quality - Yusuf Emre Akgündüz; E. Jongen; Paul P M Leseman; Janneke Plantenga (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2015)
In this article we present quasi-experimental evidence on the relation between child care subsidies and child care quality. We exploit the difference in fund- ing of private and public centers in the Netherlands. A recent subsidy cut reduced funding for private centers while funding for public centers was unaf- fected. The quality measurements are from a panel survey in which centers' quality was evaluated through classroom assessments by trained observers. Using differences-in-differences we find that the subsidy reduction caused a statistically significant decrease in quality of one fifth of a standard deviation. We also present results for nonlinear differences-in-differences estimators. The decline in quality is robust across specifications and appears to be driven by a decline in the middle of the distribution. A limitation of our data set is that our pre-reform period is short, so that we cannot perform pre-reform placebo tests.
Keywords: 330; child care subsidies; child care quality; DID; CIC